2021
DOI: 10.1021/acs.jafc.1c06022
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Biosynthesis of Farnesene Using Metabolic Engineering

Abstract: Farnesene, as an important sesquiterpene isoprenoid polymer of acetyl-CoA, is a renewable feedstock for diesel fuel, polymers, and cosmetics. It has been widely applied in agriculture, medicine, energy, and other fields. In recent years, farnesene biosynthesis is considered a green and economical approach because of its mild reaction conditions, low environmental pollution, and sustainability. Metabolic engineering has been widely applied to construct cell factories for farnesene biosynthesis. In this paper, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 120 publications
0
9
0
Order By: Relevance
“…Many previous studies have developed different strategies for rerouting the metabolic flux in S. cerevisiae to farnesene production. , Among them, modification of the MVA pathway has proven to be a powerful approach. Liu et al reported that the overexpression of all MVA pathway genes can significantly increase farnesene production in Y.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have developed different strategies for rerouting the metabolic flux in S. cerevisiae to farnesene production. , Among them, modification of the MVA pathway has proven to be a powerful approach. Liu et al reported that the overexpression of all MVA pathway genes can significantly increase farnesene production in Y.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, α-farnesene can be considered a potential protective agent in agriculture. Additionally, α-farnesene has a high demand in industrial production owing to its potential as a jet fuel substitute and precursor of high-performance polymers. , However, naturally extracted α-farnesene from plants fails to meet market needs because of an insufficient raw material supply. Hence, several efforts have been focused on biosynthesizing α-farnesene through metabolically engineered microbial hosts.…”
Section: Introductionmentioning
confidence: 99%
“…As an important sesquiterpene organic compound, farnesene has two major isomers of αand β-farnesene in nature. In particular, β-farnesene has been identified as an aphid alarm pheromone, which was first applied for pest control in agricultural protective agents (Tang et al, 2021;Liu et al, 2022a). β-Farnesene is also an ideal substitute for sustainable aviation fuels (SAFs) with characteristics of high efficiency, high calorific value, and being green renewable.…”
Section: Introductionmentioning
confidence: 99%
“…However, the drawbacks of plant extraction, such as poor yield, high production costs, the scarcity of feedstock and the severe environmental damage, restrict their industry use [ 3 , 5 , 6 ]. Researchers focus on using microbial fermentation to produce α-farnesene as a result, and numerous efficient methods have been used to modify microorganisms to enhance the biosynthesis of α-farnesene, such as enhancing the α-farnesene biosynthesis pathway, blocking the downstream α-farnesene biosynthesis pathway, rewriting the central carbon metabolism, compartmentalizing the supply ways of precursors, relieving the inhibition of cell growth and optimizing the metabolic process [ 3 , 4 , 7 , 8 , 9 ]. In the previous study, we constructed an α-farnesene high-producing strain, Pichia pastoris X33-30, by the dual regulation of cytoplasm and peroxisomes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%